Professional Development Program as Basis for Continuous Improvement among Teachers in Upland Schools - Adriano, Lyra (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigated the extent of the effects of a professional development program as a basis for continuous improvement among teachers in selected upland schools in Tanay District, Division of Rizal, during the School Year 2025–2026. The study covered eleven public elementary schools, namely: Aguho, Alas-Asin, Cayabu, Cuyambay, Daraetan, Laiban, Madilay-dilay, Magata-Manggahan, Pinagsabiran, Tablon, and Tinucan Elementary Schools. A descriptive survey research design was employed, involving one hundred (100) teachers representing the total population of teachers in the identified schools. The respondents were described in terms of age, sex, civil status, educational attainment, position title, length of service, and in-service trainings attended.A researcher-made questionnaire-checklist was utilized to determine the perceived extent of the effects of professional development programs on teachers’ continuous improvement with respect to teaching competencies, classroom management techniques, leadership capabilities, and research involvement. Documentary analysis of the teachers’ latest Individual Performance Commitment and Review (IPCR) ratings was also conducted to determine their level of work performance. Statistical tools were applied to analyze differences and relationships among variables.Findings revealed that the majority of respondents were female, aged 30–39, single, master’s degree holders, holding Teacher I positions, with 5–9 years of service, and had attended division-level trainings. Teachers perceived the effects of professional development programs on all four areas of improvement to a high extent. No significant differences were found in the perceived effects of professional development programs when grouped according to demographic and professional profile variables. Moreover, teachers’ work performance was rated as Very Satisfactory, and no significant relationship was established between the perceived effects of professional development programs and their IPCR ratings.The study concluded that professional development programs are consistently perceived as beneficial across teacher profiles, though such perceptions do not directly correlate with measured work performance. Based on the findings, a continuous improvement plan is proposed to further enhance teacher development in upland schools.